Between process and form: hybridisation of knowledge in the coworking project - Migliore, Alessandra; Manzini Ceinar, Irene; Tagliaro, Chiara (TECHNE - Journal of Technology for Architecture and Environment, 2021)
The article reflects on the contamination of professionalisms and disciplines in the architectural project. It proposes a first exploration of the concept of hybridisation of knowledge in the design of coworking spaces. The experiences of designers and managers of coworking spaces, collected through interviews, bring out multiple facets of hybridisation: (a) hybridisation of different professions and disciplines in the complex process of management and design; (b) hybridisation of the formal, morphological and typological outcome, in a space that is flexible in form, function and process. The areas of design first and then management overlap towards a transdisciplinary approach.